Gallstone Ileus-Lessons from a Missed Diagnosis - Animesh Ajit Sathe; Rajat Naresh Bhargava (Thieme Medical and Scientific Publishers Pvt. Ltd., 2023)
Gallstone ileus is an uncommon presentation in patients with acute abdomen. Its diagnosis and treatment are often delayed due to its nonspecific clinical presentation. Presence of gallstone in ileum can be difficult to detect on computed tomography (CT) as mostly they are lucent. We report the case of a 66-year-old man with a 1-day history of vomiting and abdominal bloating. Initial CT could not identify the obstructing gall stone. On the follow-up CT, there was a distal shift of obstruction site in the intestine raising suspicion of a gallstone. We discuss the imaging findings on CT and the clues to diagnosing gallstone ileus.